Tobermorite Microstructure Resulted from Reaction of Low Content of Silica of Rice Husk Ash and Quicklime Mixture - Bakri, Bakri (International Journal on Advanced Science, Engineering and Information Technology, 2018)
Tobermorite is a hydration product resulted from hydration process of cementitious material, and it has the most important role among the other hydration products in concrete and mortar because of its stiffness and strength. Most of the cementitious materials used for making concrete and mortar in the construction industry originate from the nonrenewable material. Due to the environmental issues, renewable materials such as rice husk ash are proposed to be used as supplementary or substitution for the nonrenewable cementitious material. This study aimed to investigate the presence of tobermorite resulted after hydration process of a mixture of low content silica of rice husk ash and quicklime. Rice husk ash used in this study containing silica (SiO2) of 69.42% and quicklime containing calcium oxide (CaO) of 95.75%. Samples in powder form to determine the presence of tobermorite were analyzed by using X-ray diffractometer Bruker D8 Focus and micrographs of microstructure were analyzed by using SEM JEOL 7000F. Powder samples were originated from samples in cube form of a mixture of rice husk ash and quicklime. Samples of 1 cm3 were made by using 5 mixture ratios of rice husk ash and quicklime namely 0.25:0.75, 0.35:0.65, 0.50:0.50, 0.65:0.35, and 0.75:0.25. 28 days curing time of samples needed before converted to powder form. The results of XRD analysis show that no tobermorite formation presented in a mixture ratio of 0.25:0.75and 0.35:0.6, while the presence of tobermorite formation showed in a mixture ratio of 0.50:0.50, 0.65:0.35, and 0.75:0.25. But SEM analysis found jennite microstructure, a mineral looks like a tobermorite, in a mixture of rice husk ash and quicklime at a ratio of 0.25 : 0.75.